Uso del falso tabaco (Nicotiana glauca) en diferentes dosis para el control de la mosca de la fruta (Anastrepha striata) Salache 2021. - Vilema Tigasi, Ana Johanna (2021)
This research was carried out in Latacunga canton, Cotopaxi province, Salache Bajo parish, in the Entomology laboratory of Facultad de Ciencias Agropecuarias y Recursos Naturales at Universidad Técnica de Cotopaxi, with the objective of determining the appropriate use of False tobacco extract (Nicotiana glauca) as a bioinsecticide in doses provided for the control of fruit flies (Anastrepha striata). A completely randomized design was elaborated with 5 treatments including the control where the effectiveness of doses was evaluated at concentrations of 0, 5, 10, 15 and 20 cc of false tobacco extract, which was compounded with molasses reaching 100 cc completing each of the doses, 40 individuals of fruit flies of the genus (Anastrepha striata) were chosen for each of the aforementioned doses, giving a total of 200 specimens for their respective observation and determination of the time in hours or days that this extract takes to take effect and determine their mortality. Five glass boxes were used where 40 flies were placed in each one together with sponges impregnated with doses placed in Petri dishes painted yellow, after which data were taken in the first 30 minutes, 1 hour, 2 hours and finally the days that these flies died either by ingesting the bioinsecticide based on false tobacco or by starvation with the passing of the time already specified and taken into account for data collection, Being the dose of 5 cc the most effective giving a total of 4 individuals dead in the first 30 minutes and therefore an average life of 10 days followed by the dose of 10 cc with a duration of 12 days and those of 15 and 20 cc with 14 days reflecting a repellent action on this genus of fruit fly (Anastrepha striata).